Systematic Review of Surgical and Nonsurgical Interventions in Normal Men Complaining of Small Penis Size. (23rd April 2019) - Marra, Giancarlo; Drury, Andrew; Tran, Lisa; Veale, David; Muir, Gordon H.
ABSTRACT: Introduction: Evidence on penile enhancement interventions is lacking. Nonetheless, many non–evidence-based solutions are readily available. Aim: To investigate enhancement and nonenhancement interventions in men without penile abnormalities seeking to increase penis size. Methods: We performed a systematic review with no time restrictions adhering to the PRISMA guidelines. Studies with fewer than 10 cases or including men with organic penile pathologies or previous penile surgeries were excluded. Main Outcome Measures: When available, treatment efficacy was evaluated based on patient satisfaction, penile size increase, and complications. Results: We included 17 studies, assessing a total of 21 interventions in 1, 192 men screened, with 773 followed up after nonsurgical (n = 248) or surgical (n = 525) treatment. The quality of the studies was poor in terms of methodology for patient selection and outcomes assessment. The vast majority of series reported normal penile size. Among nonsurgical treatments, extenders increased flaccid length (but by <2 cm), injectables increased girth but were associated with a high complication rate, and vacuum devices did not increase size. Surgical interventions included suspensory ligament incision (the most used method; n = 12), tissue grafting (autologous, n = 2; dermal fat, n = 3, ex vivo, n = 2), flaps (n = 2), and penile disassembly (n = 1). Some men reported a significant size increase; however, complications were not infrequent, and none of the techniques was externally validated. When provided, counseling was effective, with the majority of men coming to understand that their penis was normal and unwilling to undergo any further treatment. Conclusion: Treatment of small penis in normal men is supported by scant, low-quality evidence. Structured counseling should be always performed, with extenders eventually used by those still seeking enhancement. Injectables and surgery should remain a last option, considered unethical outside of clinical trials.